Effect of varying doses of tamoxifen on ovarian histopathology, serum VEGF, and endothelin 1 levels in ovarian hyperstimulation syndrome: an experimental study - Pala S; Atilgan R; Ozkan ZS; Kavak SB; Ilhan N; Akpolat N; Sapmaz E (Dove Medical Press, 2015)
Sehmus Pala,1 Remzi Atilgan,1 Zehra Sema Ozkan,1 Salih Burçin Kavak,1 Nevin Ilhan,2 Nusret Akpolat,3 Ekrem Sapmaz1 1Department of Obstetrics and Gynecology, 2Department of Biochemistry, 3Department of Pathology, Firat University School of Medicine, Elazig, Turkey Objective: To examine the effects of low-to-high doses of tamoxifen on ovarian histopathology, serum VEGF, and endothelin 1 levels in ovarian hyperstimulation syndrome (OHSS) in an experimental setting.Materials and methods: A total of 20 female Wistar albino rats, 22 days of age, were randomly divided into four groups. Follicle-stimulating hormone 10 IU was administered subcutaneously in 15 rats on 4 consecutive days, with OHSS induction on day 5 by 30 IU of human chorionic gonadotropin. Group 1 (n=5) comprised 35-day-old control rats, group 2 (n=5) 35-day-old OHSS rats, group 3 (n=5) 27-day-old OHSS rats receiving 1 mg/kg of oral tamoxifen for 7 days, group 4 (n=5) 27-day-old OHSS rats receiving 3 mg/kg of oral tamoxifen for 7 days. All rats were decapitated on day 35. Serum VEGF, endothelin 1, and ovarian follicular reserve were assessed in all rats. Kruskal–Wallis variance analysis and the Mann–Whitney U-test were used for statistical comparisons. A Bonferroni correction was performed to control the inflation of significance, with a significance level set at a P-value of less than 0.025.Results: Despite higher serum VEGF, endothelin 1, follicular reserve, and angiogenesis and fibrosis of the corpus luteum in the OHSS group compared to controls, these differences were not significant (P>0.025, Mann–Whitney U-test). There was a significant reduction in the ovarian follicular reserve in tamoxifen groups compared to controls (P<0.025, Mann–Whitney U-test), while angiogenesis of the corpus luteum, number of atretic follicles, fibrosis, and serum VEGF were significantly higher in rats receiving tamoxifen (P<0.025, Mann–Whitney U-test). Also, significantly lower follicular reserve and fibrosis were observed among rats in the low-dose tamoxifen group in comparison with rats in the high-dose tamoxifen group (P<0.025, Mann–Whitney U-test). No groups had a significant change in endothelin 1 levels (P>0.025, Mann–Whitney U-test).Conclusion: Tamoxifen 1 g and 3 g resulted in a dose-dependent increase in VEGF and endothelin 1 levels, and ovarian follicle reserves were significantly reduced in our experimental model. Keywords: low-to-high doses of tamoxifen, OHSS, cystic enlargement of the ovaries, hCG